1972
DOI: 10.1021/ac60315a064
|View full text |Cite
|
Sign up to set email alerts
|

Determination of glibornuride (a tolylsulfonyl urea hypoglycemic agent) in blood by differential pulse polarography

Abstract: proach to ac polarography in the harmonic multiplex mode because it replaces numerous analog circuits, which require tuning, offset adjusts, etc., by a drift-free, highly automated digital program. On the other hand, because it places minimal demands on data acquisition capability, an analog conditioning approach such as the one used in this work is favored whenever digital data acquisition rates are too slow to meet the demands of digital signal conditioning-e.g., whenever one has to operate with a slob dedic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

1973
1973
1976
1976

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Conditions for Polarographic Analysis-A polarographic analyzer' equipped with a drop timer2 was used in conjunction with a three-electrode polarographic cell comprised of a dropping mercury electrode, a saturated calomel electrode (SCE), and a platinum wire as the auxiliary electrode, as previously described (9). The drop time was 1.0 sec, and the drop mass was 2.32 mghec, where (m2/3) (t'l6) = 1.7525.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Conditions for Polarographic Analysis-A polarographic analyzer' equipped with a drop timer2 was used in conjunction with a three-electrode polarographic cell comprised of a dropping mercury electrode, a saturated calomel electrode (SCE), and a platinum wire as the auxiliary electrode, as previously described (9). The drop time was 1.0 sec, and the drop mass was 2.32 mghec, where (m2/3) (t'l6) = 1.7525.…”
mentioning
confidence: 99%
“…Transfer an 8-ml aliquot into a clean 50-ml tube, and add 2 ml Calculations-The current (microamperes) resulting from each peak and the overall recovery of each compound are determined as previously described (9), while the concentration of each component in the unknowns is determined from the respective internal standard curves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxylation at the C-3 position also occurs, resulting in the elimination of these metabolites as their glucuronide and/or sulfate conjugates. The methods were applied to the determination of blood levels of clonazepam in man following single 2-mg oral doses (29,30) and of flunitrazepam in the dog following single 2-mg/kg doses by intravenous and oral routes (29). The 7-nitro-3hydroxy analogs of clonazepam and flunitrazepam, which are also hydrolyzed to the same benzophenones (Scheme I), are removed by selective solvent extraction prior to acid hydrolysis to ensure the Tables I and II specificity of the assay for the respective parent compounds.…”
mentioning
confidence: 99%
“…A sensitive electron-capture GLC assay for the determination of bromazepam in blood, employing acid hydrolysis to the benzoylpyridine derivative (IV) (12), was not specific for bromazepam since metabolites I1 and 111, if present in blood, would also yield the same hydrolysis product (Scheme 1)and would interfere with the specificity of the assay. An improved assay was developed for the simultaneous determination of bromazepam and its MARVIN A. BROOKS, and CARL V. PUGLISI 3-hydroxy metabolite (11) as the intact 1,4-benzodiazepin-2-ones by a modification of published procedures (13,14). When using this modified procedure, it was shown that I1 was not measurable in the blood of subjects chronically treated with bromazepam.…”
mentioning
confidence: 99%